Die Universität Innsbruck in der Ära der Thun-Hohenstein'schen Reformen 1848-1860 - Aichner, Christof (Böhlau, 2018)
The book addresses the implementation of the reform of the Austrian educational system named after Minister Leo Thun-Hohenstein (1811-1888) in the years following the revolution of 1848 at the University of Innsbruck.